Refined Time-Domain Buffeting Analysis of a Long-Span Suspension Bridge in Mountainous Urban Terrain - Bo Wu; Liang-Liang Zhang; Yang Yang; Lian-Jie Liu; Zhi-Jun Ni (Advances in Civil Engineering)
The field measurements, wind tunnel tests, and numerical calculations are utilized to conduct refined time-domain buffeting analysis of a long-span suspension bridge. The wind characteristics in the mountainous urban terrain are obtained through long-term field measurements. The aerostatic force coefficients (AFCs) and aerodynamic admittance functions (AAFs) are experimentally tested in a wind tunnel. The fluctuating wind fields on the bridge are simulated by the spectral representation method. Finally, the buffeting responses are calculated in ANSYS. The influences of AAF, turbulence power spectrum, and angle of attack (AoA) on the buffeting responses are evaluated, which highlight the inaccuracies caused by empirical simplifications. To improve the buffeting performance without a considerable extra budget, minor modifications are introduced to the original design configuration. The buffeting responses are slightly reduced by increasing the ventilation rate of guardrails, and the control efficiency is better when concurrently moving the inspection rails inward. Besides, the buffeting responses are increased when considering the roughness on the girder surface. The influence mechanism of the countermeasure is analyzed using the Computational Fluid Dynamics (CFD) method, which mainly lies in the dissipation of turbulence energy around the girder. The findings can contribute to the wind-resistant analysis and optimization design for similar bridges.